2018
DOI: 10.1080/16089677.2018.1433110
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of patients with type 2 diabetes mellitus with the SEMDSA lifestyle guidelines

Abstract: Background: Type 2 diabetes mellitus (T2DM) is considered to be the fastest growing chronic disease in the world and thus multi-sectoral, population-based strategies and approaches are needed to address the modifiable risk factors involved in the development and treatment of T2DM. Evidence-based nutrition principles and recommendations are summarised by the Society for Endocrinology, Metabolism and Diabetes in South Africa (SEMDSA) into guidelines for the management of T2DM. This study aimed to determine the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Pragmatic evidence supports the efficiency of TTM on behaviour change (Hill et al, 2008), but there were mixed results found on adherence behaviour (Taylor et al, 2006;Han et al, 2020). The diabetes self-management education and support (DSMES) guidelines (Powers et al, 2015;Beck et al, 2017) and diabetes prevention program (DPP) (DPP, 2002) guidelines are freely available and reproducible for all educators' and patients' usage, yet the level of adherence to diet and physical activity remains poor among T2DM patients (Ganiyu et al, 2013;Birkinshaw et al, 2018;Aladhab and Alabbood, 2019). This situation identifies the need to investigate in-depth concerning diet and physical activity adherence further.…”
Section: Introductionmentioning
confidence: 99%
“…Pragmatic evidence supports the efficiency of TTM on behaviour change (Hill et al, 2008), but there were mixed results found on adherence behaviour (Taylor et al, 2006;Han et al, 2020). The diabetes self-management education and support (DSMES) guidelines (Powers et al, 2015;Beck et al, 2017) and diabetes prevention program (DPP) (DPP, 2002) guidelines are freely available and reproducible for all educators' and patients' usage, yet the level of adherence to diet and physical activity remains poor among T2DM patients (Ganiyu et al, 2013;Birkinshaw et al, 2018;Aladhab and Alabbood, 2019). This situation identifies the need to investigate in-depth concerning diet and physical activity adherence further.…”
Section: Introductionmentioning
confidence: 99%
“…18 In terms of clinical care, all clinicians interviewed were familiar with current guidelines on management of T2DM. 7,22 This was in contrast to other studies, where the lack of familiarity was one of the barriers to insulin initiation. 15,16 The guidelines are clear on when insulin should be initiated, but do not provide guidance on the content or timing of counselling.…”
Section: Discussionmentioning
confidence: 86%
“…Individuals could benefit from additional information about their medication, exercise and management of their stress. The SEMDSA made guidelines available for taking ownership of dietary management of patients with Type 2 diabetes (Birkenshaw, Nel & Walsh 2018 :39). The ability to appropriately accept the presence of the disease could influence the adherence to dietary recommendations and self-management practices.…”
Section: Discussion Of Findingsmentioning
confidence: 99%